Effect of pH, temperatures and carbon sources on formation of biofilm in Xanthomonas oryzae pv. oryzae - Zulkiflee, Nurul Amalina (2017)
A biofilm is any group of microorganisms in which cells stick to each other and often these cells adhere to a surface. These adherent cells are frequently embedded within a self-produced matrix of extracellular polymeric substance (EPS). Hence, the objective of this study was to determine the effect of pH, temperatures and carbon sources on biofilm formation in Xanthomonas oryzae pv. oryzae (Xoo), the causative agent of bacterial leaf blight disease of rice. To achieve the research objective, peptone sucrose agar (PSA) and microplate titer method are used to assess biofilm formation. For the pH treatment, it was indicated that the optimum pH media for biofilm production was at pH 7. For temperature treatment, it was indicated that the optimum temperature for biofilm production was at 30⁰C. Biofilm formation also increased when high glucose content in the medium. So, it can be conclude that, pH, temperatures and type of carbon sources will be significantly influence of biofilm formation in Xanthomonas oryzae pv. oryzae (Xoo).